A simulation-model of avena-fatua l (wild-oat) growth and development - Weaver, S.E.; Kropff, M.J.; Cousens, R. (Wiley, 1993)
An eco‐physiological simulation model of the growth and development of Avena fatua was parameterised and tested. The model simulates growth ofA. fatua, in kg dry matter ha‐1 day‐1 from sowing to maturity as a function of irradiance, temperature and various species characteristics. Parameter values were derived from the literature and from field experiments, including both autumn and spring sowings of A. fatua over three years at two sites in southern England. With two exceptions, a single set of parameter values was sufficient to accurately simulate the emergence, growth and development of both autumn and spring cohorts over all years and sites. The two exceptions were the result of differences between autumn and spring cohorts of A. fatua in the rate of early leaf area growth and in the relationship between specific leaf area and developmental stage.